The effect of Cu2O thickness in Perovskite Solar Cell to Power Conversion Efficiency and Its Stability. Issue 1 (May 2019) - Maryam, Siti; Mufti, Nandang; Fuad, Abdulloh; Adi Setio Laksono, Yoyok; Taufiq, Ahmad; Sunaryono
Abstract: Perovskite Solar Cell (PSC) methylammonium lead halide (CH3 NH3 PbI3 ) base is one of promising solar cell that has inexpensive materials, relatively simple and versatile fabrication high power conversion efficiency (PCE). However, perovskite CH3 NH3 PbI3 has relatively low stability due to very sensitive to polar solvents such as water, where this compound will easily decompose into PbI2 quickly. Some attempts have been made by researchers to increase the stability for example by adding Hole transport material (HTM) to prevent corrosion of the sensitizer, enhance the resistance to degradation CH3 NH3 PbI3 and improve the stability against moisture. Cuprous oxide (Cu2 O) is ones of p-type semiconductor with low electron affinity and very high hole mobility that is a potential for hole transport material in heterojunction based solar cells. The aim of this research is to investigate the effect of Cu2 O thickness as HTM in PCE and stability of perovskite solar cell. The electron transport layer (ETL) of TiO2 was synthesized by a screen-printing method on fluorine tin oxide (FTO) substrate. Perovskite CH3 NH3 PbI3 was deposited on ETL by one step spin coating, while Cu2 O was synthesized by Chemical Bath Deposition (CBD) on another FTO substrate with 5 times and 10 times dip. The stability of PSC measured by a comparison between PCE after synthesized and after stored for two months. The increasing of HTM Cu2 O Thickness raise the PCE and stability of PSC.